The effects of 5-aminolevulinic acid photodynamic therapy on the local immune response of women with cervical intraepithelial neoplasia grade 2 - Wu, Anyue; Niu, Jing; Hong, Zubei; Gu, Liying; Huang, Yuli; Qiu, Lihua (Frontiers in Immunology, 2023)
Objective To evaluate and elucidate the effects and mechanism of 5-aminolevulinic acid photodynamic therapy (ALA-PDT) on the local immune response of women with cervical intraepithelial neoplasia grade 2 (CIN2). Materials and methods Immunofluorescence staining was used to compare immune cells infiltration before and after ALA-PDT in 23 patients with CIN2. The infiltration of immune cells into the cervical tissues of patients with different outcomes was also compared at the 6-month follow-up period. Immune cell counts in samples collected before and after treatment were compared. Results We found an increased number of CD8+ T cell infiltration, an increased proportion of CD8+ T cells expressing Granzyme B (GrB), Chemokine receptor 3 (CXCR3), and CD8+ tissue-resident memory T (TRM) cells, and a decreased proportion of CD8+ T cells expressing PD-1 in patients with CIN2 compared to that before ALA-PDT. Moreover, at the 6-month follow-up, there was higher infiltration of CD8+ T and CD8+ TRM cells, higher expression of GrB and CXCR3, and lower expression of PD-1 on CD8+ T cells in the HPV clearance and CIN2 disappearance groups than in the HPV-positive and CIN2 regression groups. However, no significant difference was observed in the number of CD8+ TSCM following ALA-PDT. Conclusion ALA-PDT could activate CD8+ T cell responses by modulating the expression of CXCR3 and PD-1 in CD8+ T cells and increasing the infiltration of CD8+ TRM cells. And the infiltration of CD8+ T cells is correlated with the prognosis of CIN2.